Synthesis of gold nanoparticles via femtosecond laser ablation for applications in nanobrachytherapy - Machado, Noé Gabriel Pinheiro (2024)
Cancer remains a critical global health issue, standing as the second leading cause of death worldwide. Traditional brachytherapy, which involves the implantation of radioactive sources, offers an effective but invasive treatment method. In response to its drawbacks, nanobrachytherapy has emerged as an innovative approach, utilizing nanoparticles to deliver radiation precisely and less invasively. Gold nanoparticles are particularly suitable for this purpose due to their short half-life and favorable physical properties. This study explores the production of chemically pure gold nanoparticles, specifically coated with gum arabic (AuNP@GA), polyethylene glycol (AuNP@PEG), and silica (AuNP@SiO2) using femtosecond laser synthesis. This method involves only water, a solid gold target, and a stabilizing agent, avoiding any chemical reagents, making it a pioneering approach in the field of nanobrachytherapy. The research achieved the synthesis and nuclear activation of these nanoparticles in the IPEN IEA-R1 reactor. Among the variants, the silica-coated gold nanoparticles (AuNP@SiO2) demonstrated superior stability following nuclear activation. The resultant AuNP@SiO2 colloidal suspension was exceptionally stable, evidenced by a Zeta Potential of -72.0 mV. Transmission electron microscopy (TEM) confirmed the production of nanoparticles with an average size of 16 nm. These findings highlight the potential of AuNP@SiO2 for use in nanobrachytherapy, offering a novel nanomaterial and highly stable for application in cancer treatment. This breakthrough sets a new possibility for producing nanoparticles in a sustainable manner and with high purity, aligning technological innovation with the crucial need for new nanomaterials for cancer treatment.